Determination of Phenolic Total, Flavonoid Total, Antioxidant Assay and Inhibition of Xanthine Oxidase Enzyme Activity Kemloko Fruits Extract (Phyllanthus Embilica. L) - Wirasti Wirasti; Khusna Santika Rahmasari; Isyti'aroh (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2024)
People use Kemloko Fruits as sweets and some also use it as a herbal medicine to reduce uric acid. The sour-tasting Kemloko fruit contains a lot of ascorbic acid. Ascorbic acid and ingredients contained in it have the effect of preventing or reducing uric acid levels. The aim of this research was to treat the antioxidant effect and inhibitory of the xanthine oxidase enzyme Kemloko Fruit extract, as well as determine the phenolic total and flavonoid total levels. The method used to make Kemloko fruit extract uses maceration with ethanol 96% solvent. The phytochemical screening method uses an in-tube reaction for flavonoid content using the Shinoda test, alkaloids using the Dregendorf reagent, saponins using the foam test and terpenoids/steroids using the Liebermann Burchard reagent. Meanwhile, the methods for determining phenolics and flavonoids total are the colorimetric used spectrophotometry UV-Vis, the DPPH methods for antioxidant assay, and measurenment of inhibiting xanthin oxidase activity using a microplate at a wavelength of 375 nm. Qualitative data produced by the ethanol extract of Kemloko fruit contains tannins, flavonoids, alkaloids, terpenoids, saponins and glycosides. Meanwhile, Quantitative data showed that the phenolic and flavonoid total levels were 1465.63±0.003 mgGAE/g extract and 9.52±0.001 µg/mL, respectively, as well as the IC50 for xanthin oxidase enzyme inhibition of 20.65 µg/mL and the IC50 antioxidant power of 9.49 ±0.0007 µg/mL. Kemloko fruit ethanol extract contains tannins, flavonoids, alkaloids, terpenoids, saponins and glycosides has inhibitor activity against xanthine oxidase and antioxidant is a strong.